New taxa and records of flat bugs (Hemiptera: Heteroptera: Aradidae) from Hainan of China XIAOSHUAN BAI (P.R. China), ERNST HEISS (Austria) & WANZHI CAI (P.R. China) - Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2011)
From Hainan Province, southern China, a new genus of Carventinae: Caiaptera n. gen with the species C. picea n. sp. and a new genus of Mezirinae: Hainanmezira n. gen with the species H. latiscutellata n. sp. as well as Notoplocaptera hainanensis n. sp., are described and illustrated. Additional records are given, and a list of species recorded to date from this province is presented.